The Implementation Of The Simple Multi Attribute Rating Technique (SMART) Method In Determining The Candidates Of Social Assistance Recipients In Bajak 1 Village Based On Decision Support System - Dari, Erika Dwi Ulan; Yulianti , Liza; Prahasti , Prahasti (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
Bajak 1 Village is a village located in Taba Penanjung Sub-District of Central Bengkulu and has a large population. In making decisions about social assistance recipients in Bajak 1 village, currently still using the manual method by collecting data from existing residents. problems in decision making and the possibility of people's data being mixed up therefore they are wrong in making decisions. The method that can be used in making decisions for prospective recipients of Social Assistance (Bansos) is the SMART (Simple Multi Attribute Rating Technique) method. The SMART method is a multi-attribute and flexible decision-making technique that can assist the village in making decisions quickly and accurately. To determine prospective recipients of social assistance based on 3 criteria, namely: occupation, income, and number of dependents. Based on these 3 criteria, a Decision Support System was developed using the SMART method. Decision Support System is a computer system that processes data into information and decisions. With the design of a Decision Support System to determine prospective recipients of social assistance using the SMART method, Bajak 1 Village can be assisted in making decisions for prospective recipients of social assistance. .